ANALYSIS OF COMPENSATION AND JOB SATISFACTION, ON THE PERFORMANCE OF KPSBU LEMBANG EMPLOYEES - Hayla, Nickita; Abdullah, Lutfiah Salma; Hardiansyah, Anwar; Agustina, Rhena; Permatasari, Putri; dyahrini, Wien (CENTRAL ASIA AND THE CAUCASUS, 2022)
Human Resources play an important role in a company. Providing the resources needed enable companies to compete with other in achieving goals. The company strives to increase employee productivity to improve employee performance. KPSBU Lembang or North Bandung Cattle Breeders Cooperative is a single primary cooperative business as an institution that has a role and provides good services for farmers in Lembang sub-district. To improve employee performance, it is necessary to analyze employee compensation and job satisfaction. Researchers conducted a survey of 104 respondents of KPSBU Lembang employees. A simple random sampling technique is a random sampling technique in the population. This study uses the proposed Multiple Linear Regression method to analyze the correctness of the data in order to know the influence between free variables and bound variables. The results of this study can be concluded that compensation variables and simultaneous job satisfaction that have a significant effect on employee performance are proven using the results of simultaneous tests (test f) and partial tests (t test).